Composição química, atividade antibacteriana e sinérgica do óleo essencial de Lippia Sidoides contra isolados clínicos de Acinetobacter Baumannii multirresistentes - Lopes, Letícia Bandeira Mascarenhas (2024)
Antibiotics, since their discovery, have been extensively used as a fundamental therapeutic tool against bacterial infections. However, the indiscriminate use of these medications has resulted in the emergence of progressively more resistant bacterial strains. Given this scenario, it is essential to search for new natural substances with antimicrobial properties. The biological activities attributed to the essential oil of Lippia sidoides are mainly related to its major chemical component, thymol. The objective of the present study was to valuate the antimicrobial and synergistic activity with conventional antibiotics of Lippia sidoides essential oil (OELS) against clinical isolates of multidrug-resistant Acinetobacter baumannii. The OELS, extracted by hydrodistillation, had its antibacterial activity determined using the disk-diffusion and broth microdilution method to determine the minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Synergistic activity was evaluated using combinations of OELS with antibiotics: ciprofloxacin (CIP), meropenen (MPN) and ceftriaxone (CRO). The OELS had a yield of 0.97% w/w, and its chemical composition had thymol (76.16%), p-Cymene (8.18%) and β-Caryophyllene (5.43%) as its main constituents. All strains were sensitive to OELS with inhibition zones between 21.67 and 33.33 mm. The OELS showed MIC of 500 µg/mL for all strains and MBC of 500 µg/mL to 2000 µg/mL. The synergistic, additive and indifferent interaction of OELS when combined with antibiotics was also observed. Our results indicate potential of OELS. However, more research is needed to corroborate its biotechnological potential, which could be a promising alternative in the treatment and prevention of infectious diseases.